السكن الحضري ببلدة البردي: (دراسة تحليلية لواقــــع الإسكان) - عبدالسلام , بشير محـمد (Tobruk University Journal of Social and Human Sciences, 2024)
For humans, urban housing constitutes protection from environmental hazards, and guarantees continuity of life and development, that is, it fulfills the minimum requirements necessary for life, so the study of urban housing throughout the country is a necessity because it is one of the basic problems that must be addressed, so the study aimed to identify The reality of the existing housing in the town of Al-Bardi, as well as the estimation of the housing need for the study area (Al-Bardi).And the future prospects for it, and the importance of the study included identifying the housing patterns in the town, and the problem of the study lies in the lack of housing units compared to the number of the town's population, which is reflected in the physical characteristics of the housing, i. Residential areas in the study area. The study followed the scientific method of collecting data objectively and conducting a field survey to complete the deficiency in the available database, as well as making use of the results of previous studies in the field of geography of cities related to the subject of the study. The study also followed the descriptive approach to identify the natural and human characteristics of the study area, the historical approach to trace the stages of development of its population that the town went through, then the quantitative analysis approach in dealing with the numerical variables of the subject of the study. The study dealt with three axes, the first axis: the population of the town and the second axis: characteristics. Material housing and the third axis: residential demand for the study area and future prospects. The study concluded with results: Neglecting development in rural areas throughout the country, including the town of Al-Bardi, and concentrating economic projects in urban areas, which led to an increase in immigration and the displacement of the town’s residents. The study concluded that work was required to require official authorities to prepare and equip new housing plans, and to grant real estate loans that facilitate the process of building and constructing residential units. that comply with the housing standard.